Pharmacogenetically tailored treatments for heart disease - Vafiadaki, E.; Arvanitis, DA; Kranias, EG; Sanoudou, D. (Curr Pharm DesCurr Pharm DesCurr Pharm Des, 2010)
Heart disease represents the primary cause of death worldwide, with mortality rates being predicted to remain constant within the next couple of decades. Cardiac disease treatment currently includes the administration of drugs, predominantly aiming at improving heart performance, through controlling heart rhythm, blood pressure, as well as reducing cholesterol and blood clotting. Despite, however, the medical advances that have lead towards a better understanding of heart disease pathophysiology and the development of new therapeutic approaches, the degree of success of the available drug therapies varies among patients. The existence of polymorphisms in a number of genes has been shown to result in differences in pharmacokinetics, pharmacodynamics and drug metabolism and have therefore been associated with response to drug treatment. The occurrence of adverse drug reactions that may lead to drug-induced toxicity represents another factor influencing outcome of therapeutic treatment. While the influence of genetic polymorphisms in patient's response to heart disease drugs is being unveiled, the rapidly evolving field of pharmacogenetics is promising to aid clinicians in choosing the best suited drug/dose for each patient and the pharmaceutical companies in the design of better targeted, more effective new chemical compounds. In the near future individualized, targeted therapy will become part of clinical care routine maximizing patient therapeutic benefits and minimizing risks of adverse effects.
Vafiadaki, ElizabethArvanitis, Demetrios AKranias, Evangelia GSanoudou, DespinaengResearch Support, Non-U.S. Gov'tReviewUnited Arab Emirates2010/05/13 06:00Curr Pharm Des. 2010;16(20):2194-213. doi: 10.2174/138161210791792796.
Keywords: *Drug-Related Side Effects and Adverse Reactions/genetics/*prevention & control; Anti-Arrhythmia Agents/adverse effects/therapeutic use; Anticholesteremic Agents/adverse effects/therapeutic use; Anticoagulants/adverse effects/therapeutic use; Antihypertensive Agents/adverse effects/therapeutic use; drug design; Drug Therapy/methods; Heart Diseases/*drug therapy/genetics; Humans; Molecular Targeted Therapy; Pharmacogenetics/*methods; Polymorphism, Genetic/drug effects; Precision Medicine/*methods